EVALUATION OF ANTI-STRESS ACTIVITY OF ETHANOLIC EXTRACTS OF TERMINALIA CATAPPA L. IN SWISS ALBINO MICE - Ansari, Imtiyaz; Sorte, Rajeshwari Shashikant (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of the study was to evaluate the anti-stress activity of ethanolic extract of Terminalia catappa L. in Swiss albino mice. Methods: The extract used in this study was prepared by Soxhlet extraction of fresh dried leaves of T. catappa L. using ethanol as an extraction solvent. Stress is involved in the pathogenesis of a variety of diseases including hypertension, peptic ulcer, immunodepression, reproductive dysfunction, and behavior disorder. Overload of stress increases free radicals, produces damage to neuronal receptors and a variety of tissues. In this experimental research study two models, namely, forced swim test (FST) and tail suspension test (TST) were used for the screening of anti-stress activity. 50, 100, and 200 mg/kg ethanolic extracts of T. catappa L. were given orally, while 2mg/kg of Diazepam which acts as a standard was given intraperitoneally. The data obtained were analyzed by one-way ANOVA, followed by Dunnett's test. p<0.05 was considered to be significant. Result: The entire three test groups of the ethanolic extract of leaves of T. catappa L. showed decrease in immobility time in both FST (immobility for 42.5±3.5 s and mobility at 197.5±3.5 s) against diazepam (immobility 82.6±4.17 s and mobility at 157.3±4.17 s) and TST (92±2.28 s and mobility at 148±2.28) when compared against control as well as against diazepam (116.3±2.73 s and mobility at 123.6±2.73) which was used as a standard. Conclusion: There is substantial evidence that flavonoids play an active role in providing anti-stress activity. This study is an attempt to find out the alternative medication for treating chronic stress with single medication which was shown a beneficial effect in animal models, may be useful for curing symptoms of stress.